Willingness to take COVID-19 Vaccination among People Living with HIV/AIDS on Anti-Retroviral Therapy and Associated Factors in Woldia Comprehensive Specialized Hospital, Woldia, Ethiopia - Abayneh Tunta; Mulu Shiferaw; Habtamu Mesele; Woldeteklehaymanot Kassahun; Fissha Yehualaw; Atitegeb Abera (International Journal of Sexually Transmitted Diseases, 2023)
Background HIV causes immunosuppression, which reduces the body's immunity to diseases like COVID-19 by decreasing CD4 cells. The goal of this study is to determine whether persons living with HIV/AIDS (PLWHA) who are using anti-retroviral therapy (ART) are willing to accept the Coronavirus illness 2019 vaccination and the factors that influence their decision. Method From February 15 to March 15, 2022, 332 PLWHA on ART participated in this facility-based cross-sectional study. The correlation of outcome variables with predictors was investigated using binary and multivariable logistic regression. Result Of the 332 study participants, 110 (33.1 %) and 118 (35.5 %) had poor knowledge and a negative attitude toward the COVID-19 vaccination, respectively. Approximately 31 (9.3%) of study participants believe ART medications can also prevent COVID-19 infection. The willingness to receive the COVID-19 vaccine was 66.3 % with a 95 % confidence interval (60.9, 71.5). Knowledge, attitude, educational status, marital status, residency, duration, and monthly income were all significant predictors of willingness to receive COVID-19 vaccination. Conclusion Increased sensitization regarding the necessity of vaccines and the negative consequences of diseases, particularly among PLWHA, should be emphasized in the preparation of the COVID-19 immunization campaign involving prominent individuals such as health professionals and religious leaders.
Keywords: Sexually transmitted infections